The Influence of Machiavellian Personality, Workload, and Love of Money on Dysfunctional Auditor Behavior with Emotional Spiritual Quotient as a Moderating Variable - Suryawibawa, Ida Bagus Oka; Wirakusuma , Made Gede; Budiasih, I Gusti Ayu Nyoman; Erawati, Ni Made Adi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study empirically examines the influence of Machiavellian personality, workload, and love of money on dysfunctional auditor behavior, with Emotional Spiritual Quotient (ESQ) as a moderator. A purposive sampling method was used, and data were collected via a survey questionnaire, then analyzed using the Partial Least Square (PLS) approach. Results indicate that Machiavellian personality and increased workload positively influence unethical behavior, whereas love of money negatively impacts it, promoting adherence to ethical standards. ESQ moderates these effects by reducing the impact of Machiavellianism and high workload on unethical behavior while enhancing the ethical influence of financial motivation. These findings underscore the critical role of ESQ in fostering ethical conduct among auditors.